The Equestrian Officers of the Roman Imperial Army - Devijver, H., (Classical Studies - Book Archive pre-2000., 1989)
The papers offered here by Hubert Devijver are the narrative counterpart to his Prosopographia Militiarum Equestrium. They bring to life the careers, the social and geographical origins, the tasks and status symbols of these men as well as the monuments on which our knowledge of them is based. The Equestrian Officers and their Monuments is an original contribution for this volume. Enhanced by the indices, this book helps us understand the social class and military role of Rome's equestrian officers.